OCCURRENCE AND SIGNIFICANCE OF SERPENTINITE-HOSTED, TALC- AND AMPHIBOLE-RICH FAULT ROCKS IN MODERN OCEANIC SETTINGS AND OPHIOLITE COMPLEXES: AN OVERVIEW - Boschi, Chiara; Früh-Green, Gretchen L.; Escartín, Javier (Ofioliti, 2024)
This paper reviews the occurrence and significance of talc- and amphibole-rich fault rocks developed in mafic-ultramafic sequences and evaluates their role in deformation and alteration of the oceanic lithosphere from different tectonic settings (from spreading mid-ocean ridges up to orogenic belts). Recently, talc and amphibole-rich fault rocks have been sampled and studied from detachment fault surfaces along slow and ultra-slow spreading mid-ocean ridges, and constraining the conditions of deformation and strain localization during the evolution of oceanic core complexes. These rocks are documented not only in oceanic core complexes, but also in other oceanic fracture zones where ultramafic rocks are exposed on the seafloor, while only few occurrences have been reported in ophiolite sequences. Samples recovered in situ in oceanic settings record heterogeneous deformation (crystal-plastic to cataclastic) under greenschist- facies conditions and are commonly restricted to localized shear zones (< 200 m) and are associated with intense talc-amphibole metasomatism. The presence of mechanically weak minerals, such as talc, serpentine and chlorite, may be critical to the development of such fault zones and may enhance unroofing of upper mantle peridotites and lower crustal gabbroic rocks during seafloor spreading. Talc in particular may be influential in lubricating and softening mylonitic shear zones and can lead to strain localization and focused hydrothermal circulation along such faults. The rheology of these rocks, and its evolution during dehydration reactions could play an important role also in subduction-zone processes and during the formation of ultramafic orogenic belts. Here, we review the occurrence and significance of talc- and amphibole-rich fault rocks in different tectonic settings on the seafloor and evaluate their role in deformation and alteration of the oceanic lithosphere.